Transport and pandemic experiences - Attard, Maria; Mulley, Corinne (Transport and sustainability ;, 2022)
The COVID-19 pandemic showed how transport plays a role in societal responses to global events at all levels, from governments to transport operators and individuals. Transport and Pandemic Experiences consolidates these lessons from a range of geographies and practices. Attard and Mulley bring together leading experts in the field, examining various entities in their response to the coronavirus pandemic, using the experience of COVID-19 to inform issues of resilience and policy. Chapters provide an in-depth analysis of how the impact of the pandemic varied between demographic groups and global location, between passenger and freight modes, highlighting how transport and travel behaviour changed. Along with providing an overview of policy responses to the pandemic from the freight and air transport sector, to analysing the development of working-from-home policies with their inherent effects on public transport, Transport and Pandemic Experiences discusses how the accumulated knowledge of the pandemic needs to be capitalised in our fight against climate change and helps to identify future research imperatives for better understanding and greater policy transferability. The Transport and Sustainability series addresses the important nexus between transport and sustainability containing volumes dealing with a wide range of issues relating to transport, its impact in economic, social, and environmental spheres, and its interaction with other policy sectors.